1982
DOI: 10.1136/jcp.35.6.625
|View full text |Cite
|
Sign up to set email alerts
|

Value of plasma calcium, phosphate, and alkaline phosphatase measurements in the diagnosis of histological osteomalacia

Abstract: SUMMARY Plasma calcium and phosphate concentrations and alkaline phosphatase activities were examined retrospectively in 50 patients with histologically proven osteomalacia and 50 age-and sexmatched control subjects with normal bone histology. An abnormal plasma alkaline phosphatase activity was more useful than an abnormal plasma calcium or phosphate concentration in distinguishing between normal and osteomalacic subjects, producing a false-negative rate of 140% and a falsepositive rate of 8 %. False-negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 9 publications
4
25
0
4
Order By: Relevance
“…Plasma ALP activity appears to be a sensitive single test in the past which acceptably predicts the presence or absence of histological osteomalacia [20]. We found that the ALP levels were significantly correlated with ASDAS-CRP and bone turnover biomarkers.…”
Section: Discussion:-supporting
confidence: 53%
“…Plasma ALP activity appears to be a sensitive single test in the past which acceptably predicts the presence or absence of histological osteomalacia [20]. We found that the ALP levels were significantly correlated with ASDAS-CRP and bone turnover biomarkers.…”
Section: Discussion:-supporting
confidence: 53%
“…Elevated alkaline phosphatase is a useful biochemical test to screen for osteomalacia in celiacs, as it is in the general population [39,95,96]. Elevated alkaline phosphatase is also independently associated with clinical features of malabsorption in adults newly diagnosed with celiac disease [39].…”
Section: Metabolic Bone Disease and Fracture Riskmentioning
confidence: 99%
“…It is essentially a histological diagnosis and may exist in the absence of biochemical and radiological abnormalities (21). It is characterized by an impairment of bone mineralization.…”
Section: Histomorphometric Findings In Clinical Disorders Osteomalaciamentioning
confidence: 99%